Recovering the Momentum in Poverty Education and Rural Development: Southeast Asia at the Turn of the Century - Morales, Honoracio (Kasarinlan: Philippine Journal of Third World Studies; Vol 15 No 1 (2000): Economies in Flux, 2009)
The Southeast Asian bid for an Asian crisis recovery has received less acclaim than criticism. Southeast Asia is still referred to as “a haven of sick economies.” True or not, the region must move forward, exert a collective effort in order to eliminate poverty and boost rural development. Countries, according to the author, should strengthen the flow of information and to level off in terms of best practices in poverty eradication and rural development. The proposed Convergence Strategy, which presents a plan to share experiences, capabilities, resources and expertise in a focused area approach in key poverty stricken regions, and the ASEAN Anti-Poverty Fund, are steps in the right direction. Beginning at the conference level, Southeast Asia must recognize the principle of shared growth and the need to work closely together if it is to recover from any crisis.